Millions of cats - Gag, Wanda (New York : Coward McCann, 1977)
"Millions and billions and trillions of cats" live on a high hill and eventually they eat each other up until only one is left.
Child Study Children's Book Committee
Newbery Medal/Honor
Wilson's Children
3.6
K-3
K-3
Keywords: Cats -- Fiction; Cats -- Fiction